병원 원무행정근무자의 직무소진이 직무만족과 이직의도에 미치는 영향 - 남진영; Jin Young Nam; 손명세; Myong Sei Sohn; 강대용; Dae Ryong Kang; 유승흠; Seung Hum Yu (보건정보통계학회지, 2014)
Objectives: The purpose of study was to find the influence of job burnout on job satisfaction and turnover intention among admission and discharging employees working in hospital. Methods: The 241 employees who work at the admission and discharging department in 8 general hospital with more than 500 beds in Seoul and Gyeounggi province were surveyed from October 18, 2010 for 4 weeks. Descriptive statistics was used to understand general characteristics of subjects; the t-test and one way ANOVA followed by Tukey’s HSD test were used for analysis of the job burnout according to the general characteristics, and multiple regression was employed to find the factors of job burnout afecting job satisfaction and turnover intention, respectively. Results: First, the degrees of job burnout differ according to the general characteristics. The level of job burnout tends to be high among the population of younger age, college graduates, and employees whose number of years of service is between 3 and 10. Second, the level of job satisfaction decreases as the level of job burnout increases. Third, The level of turnover intention tends to increase as the level of job burnout increases. Conclusions: Based on the result of this study, hospitals may make an effort to lower the job burnout by improving the system of human resource management. Such effort may include prevention of falling into a routine through job rotation and continuing education, and creation of sense of belonging through timely promotion.